Angiopoietin-like protein 4 in bovine physiology - Li, Shihhui (Kansas State University, 2011)
Angiopoietin-like protein 4 (ANGPTL4) is a 55-kDa secreted glycoprotein which is an important factor for regulation of energy and lipid metabolism. Plasma ANGPTL4 has the ability to inhibit lipoprotein lipase (LPL) function by preventing it from catalyzing hydrolysis of lipoprotein triglyceride, which contributes to ANGPTL4’s ability to decrease fat storage. Furthermore, research in mice suggests that gut microbes suppress gastrointestinal ANGPTL4 production, and that decreased plasma ANGPTL4 concentrations promote fat storage. In our previous work, we found that bovine ruminal epithelial cells expressed ANGPTL4 to a greater extent than liver hepatocytes, which are usually considered the predominant source of circulating ANGPTL4. Therefore, 3 studies were conducted to evaluate the hypothesis that ruminal expression and plasma concentrations of ANGPTL4 could be influenced by alterations in ruminal fermentation. The first and second studies utilized dietary treatments intended to alter ruminal fermentability. Diets with relatively low or high forage content were fed to 12 non-lactating dairy cows (study 1) and 8 beef cattle (study 2) prior to collection of ruminal fluid and ruminal tissue samples. The results suggested that increasing the dietary concentrate decreased ruminal expression of ANGPTL4 but did not significantly alter plasma ANGPTL4 concentrations. The third study was designed to assess whether effects of diet fermentability on ruminal ANGPTL4 synthesis are mediated by changes in volatile fatty acid concentrations. In this study, 6 lactating cows were infused with acetate, propionate, or butyrate in a Latin square design. Results showed that ANGPTL4 expression was not significantly altered by volatile fatty acid infusions, but that expression was correlated with ruminal pH and total volatile fatty acid concentration. The mechanism by which ANGPTL4 regulates intracellular lipid metabolism also remains unclear. Although ANGPTL4 is known to associate with β1 and β5 integrins, it is unknown if these extracellular matrix proteins mediate the effects of ANGPTL4 in adipose tissue or muscle. The objective of the last experiment was to detect the ANGPTL4 receptor or mediator in muscle satellite cells and adipose tissue. We successfully expressed recombinant bovine ANGPTL4 with a cell free glycoprotein synthesis system. However, we did not detect the ANGPTL4–receptor complex following exposure to bovine adipose tissue explants or cultured bovine muscle satellite cells. Overall, these research projects determined that the ruminal ANGPTL4 production is influenced by fermentation, but it remains unclear whether fermentation products or direct host/microbe interactions are responsible. Finally, it will be important to identify the ANGPTL4 receptor or mediator to better understand the downstream regulatory mechanisms involved in mediating the metabolic effects of ANGPTL4.
Keywords: ANGPTL4; Cattle; Volatile fatty acids; Receptor; Mediator; Protein synthesis; Animal Sciences (0475)